Village Economics Acceleration: Evaluation of Business Strategy Schemes in The Retail Business - Mega Barokatul Fajri; Rizky Wahyudha Rosiawan; Jennifer Farihatul Bait (Universitas Muhammadiyah Jakarta, 2025)
Lamongan Regency's economic growth 2020 decreased from 5.5 percent to -2.26 percent, so the district government tried to boost the regional revenue growth rate through BUMDes (Village Owned Enterprises). The Village Community Empowerment Service (PMD) established LA Mart as a local retail business managed by BUMDes in 2018. The existence of LA Mart is a strategic step to accelerate the movement of the village economy. Among the many LA Marts that have been established since being initiated in 2018, there are only five LA Marts that have survived and exist throughout the Lamongan district today. This study aims to evaluate the current business strategy of LA Mart and provide solutions in the form of updating relevant strategies by LA Mart. Data collection methods used in this research include interviews, document analysis, and observation. The data analysis used is a qualitative descriptive analysis by evaluating and comparing the strategies used, using a business strategy approach including Business Model Canvas (BMC), Value Chain, and Porter's Five Generic Strategy at LA Mart in Lamongan. The results of this study showed that the current LA Mart business has used a combination strategy between low prices and differentiation strategies. LA Mart can indirectly increase the market share of the village economy and provide opportunities for the community and MSMEs to innovate and produce competitive products.